University Admissions System in Saudi Arabia, United States, United Kingdom, Singapore: A Comparative Study - Al-luhaidan, Sondos Saleh; Al-Qahtani, Aroub Saad; Al-Oraini, Ghada Mohammed; Al-Tuwaijri, Fatimah Abdulaziz (Journal of Educational and Psychological Sciences, 2021)
The study aims to identify the system of university admission in the Kingdom of Saudi Arabia, the United States, Britain, and Singapore, to monitor the similarities and differences between the admission systems in the countries subject to comparison, and to present proposals that could contribute to the development of the university admission system in the Kingdom of Saudi Arabia in light of the American, British and Singaporean experience. The descriptive comparative approach was used, as it is appropriate to the nature of the study and its objectives. Based on the study's proposals, a number of proposals have been made to develop the university admission system in Saudi Arabia: Decentralization of admission systems, taking into account psychological and behavioral aspects, and giving preference to highly qualified students who won global awards. The researchers recommend conducting more comparative studies aimed at identifying the admission system for university education in Saudi Arabia in different comparative countries, and conducting a descriptive study of the admission system in Saudi universities.
Keywords: Reality; Admission system; University education; Comparative study